Implementasi Metode SISDAMAS Pada KKN Nusantara Moderasi Beragana Di Desa Babakanmulya Kec. Cigugur Kab. Kuningan - Addiva Hadid, Risyad; huda, Uu Nurul; Oktavia, Churin; Soliah, Seli; Sawitri, Wahyuni (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
This article discusses the implementation of the SISDAMAS method in the Nusantara Religious Moderation Community Service (KKN) program in Babakanmulya Village, Cigugur District, Kuningan Regency. The SISDAMAS method used focuses on community empowerment through active participation in every stage of the activity, from identifying needs to evaluating the program. The results of the study showed that the people of Babakanmulya Village responded positively to this program. They felt a significant impact in increasing the capacity of human resources, especially in the fields of education and economy. Close collaboration between students, the community, and the village government also succeeded in creating strong synergy, ensuring the success and sustainability of the program. This program succeeded in improving the skills and awareness of the community in managing local resources and strengthening social relations in the village.